Perbandingan Angka Cakupan Imunisasi Dasar Anak Sebelum, Selama dan Setelah Pandemi Covid-19 - Leokuna, Irene Primagdasary; Sitompul, Monalisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to provide a clear picture of the impact of the Covid-19 pandemic on children's basic immunization coverage at the Parongpong Community Health Center, West Bandung Regency from 2019-2023. The research uses a quantitative descriptive approach with sampling techniques using methodstotal sampling. The data used is secondary data from monthly reports of routine immunization results every month. The research results show that the basic immunization coverage rate for children in the Parongpong Community Health Center working area before the 2019 Covid-19 pandemic had good coverage with the highest coverage in December amounting to 1237 (115%). In 2020, during the pandemic, basic immunization coverage for children experienced a significant decline with the highest coverage in January being only 514 children (48%) and in 2021 increasing with the highest coverage being 953 children (88%). In 2022 there will be an insignificant decline. After the Covid-19 Pandemic in 2023, the figure for basic immunization coverage among children showed an increase of 88% or around 953 children were vaccinated. Conclusion, there is a comparison of basic immunization coverage rates for children before, during and after the Covid-19 pandemic. This shows the need for special attention in efforts to restore and increase children's basic immunization coverage after the pandemic. Keywords: Immunization Coverage, Covid-19, Basic Immunization